The correlations between kinematic profiles and cerebral hemodynamics suggest changes of motor coordination in single and bilateral finger movement - Zhou, Guangquan; Chen, Yuzhao; Wang, Xiaohan; Wei, Hao; Huang, Qinghua; Li, Le (Frontiers in Human Neuroscience, 2022)
Objective: The correlation between the performance of coordination movement and the brain activity is still not fully understood. The current study was aimed to identify activated brain regions and brain network connectivity changes for several coordinated finger movements with different difficulty levels and to correlate the brain hemodynamics and connectivity with kinematic performance. Methods: Twenty-one right-dominant-handed subjects were recruited and asked to completed circular motions of single and bilateral fingers in the same direction (in-phase, IP) and in opposite directions (anti-phase, AP) on a plane. Kinematic data including radius and angular velocity at each task and synchronized blood oxygen concentration data using functional near-infrared spectroscopy (fNIRS) were recorded covering six brain regions including the prefrontal cortex, motor cortex and occipital lobes. General linear model was used to locate activated brain regions, and changes compared with baseline in blood oxygen concentration were used to evaluate the degree of brain region activation. Small-world properties, clustering coefficients, and efficiency were used to measure information interaction in brain activity during the movement. Result: It was found that radius error of dominant hand was significantly lower than that of the non-dominant hand (p<0.001) in both clockwise and counterclockwise movement. The fNIRS results confirmed that the contralateral brain region was activated during single finger movement and the dominant motor area was activated in IP movement, while both motor areas were activated simultaneously in AP movement. Δhbo were weakly correlated with radius errors (p=0.002). Brain information interaction in IP movement was significantly larger than that from AP movement in brain network (p<0.02) in right prefrontal cortex. Brain activity in right motor cortex reduces motor performance (p<0.001) while the right prefrontal cortex region promotes it (p<0.05). Conclusion: Our results suggest there was a significant correlation between motion performance and brain activation level, as well as between motion deviation and brain functional connectivity. The findings may provide a basis for further exploration of the operation of complex brain networks.